Illness experience and adjustment to treatment in hypertrophic cardiomyopathy patients undergoing cardiac rehabilitation: qualitative study. (29th July 2021) - Mierzynska, A; Sadowski, K; Piotrowicz, E; Wolszakiewicz, J; Lech, A; Dabrowski, M; Klopotowski, M; Piotrowicz, R
Abstract: Funding Acknowledgements: Study No. 2.1/I/17, Sadowski, K. MD Background. Hypertrophic cardiomyopathy (HCM) is an hereditary disease in which the heart muscle becomes abnormally thick, which makes it harder for the heart to pump blood. Some people with HCM experience medical complications, including heart failure or sudden cardiac death (SCD). Due to lack of efficient causal treatment, the goal of HCM treatment is to relieve symptoms, slow down disease development and prevent SCD. For many years one of the major lifestyle recommendations for HCM patients was to refrain from excessive physical activity and stressful situations. At the same time, there is multiple scientific evidence that cardiac rehabilitation and regular physical activity can be beneficial in terms of treatment outcome and survival in cardiac patients. Nevertheless, data on adjustment and physical activity among HCM patients are scarce. Purpose. The presented study is a part of research on the effectiveness and safety of cardiac rehabilitation in HCM patients. This part aims to assess illness perception and adjustment to treatment among patients with HCM. Method. The study is an experimental randomized control trial (RCT). In part related to adjustment and mental health there are quantitative and qualitative measures used: questionnaires related to general health, illness perception, level of stress, adherence to treatment, and semi-structured interviews performed to assess patients' concerns regarding illness identity, the impact of HCM on everyday life, and expectations of themselves and the medical team. The entire study population consists of 60 participants with HCM (cardiac rehabilitation/telerehabilitation vs usual care). Quantitative data will be analysed using appropriate tests (e.g. t-Student, regression analysis) and qualitative data will be analysed using Interpretative Phenomenological Analysis. Results. Preliminary results evaluate adjustment to treatment based on patients" experience and illness perception. The group for the qualitative study consists of 20 participants (M = 51, 70; SD = 11, 07; 13 F/ 5 M). Starting the treatment often led to intense distress because 70% of them have been diagnosed accidentally (20% after diagnosis or death of a family member). 20% of participants describe HCM using negative terms, and patients' identity of HCM fall along a continuum from "curse"/"nightmare" to "value"/"relief". Patients' adjustment is influenced the most by "being a role model for relatives struggling with HCM" and „adapting to barriers", and the most important expectation toward medical professionals was to be "approachable" and „attentive", which strenghtened the sense of security in threatening medical situations. Conclusions. Although many patients identify HCM as a burden, their adjustment to illness is mostly related to their need for being a positive role model for relatives with HCM. A therapeutic alliance with the medical team and experiencing kindness were the most important for the sense of security and being well treated.